Illegal Content Monitoring on Social Platforms - Jain, Tarun; Hazra, Jishnu; Cheng, T. C. Edwin (Production and Operations Management, 2020)
Illegal content uploads on social platforms have grown rapidly in recent years. While previous research has studied various enforcement efforts to remove illegal content, we consider such enforcement efforts in the setting where the content is sold through a platform firm. Furthermore, we consider the situation in which along with the subscription‐based legal content on the platform, there is free illegal content that may generate revenues through advertisements for the platform. Specifically, we analyze three scenarios of illegal content monitoring: (i) only the content developer monitors, (ii) only the platform firm monitors, and (iii) both the content developer and platform firm monitor the illegal content. We find that, under certain conditions, it is beneficial for the platform firm to exert a higher monitoring effort than the content developer even though the former may gain advertisement revenues through the display of illegal content. In addition, while it is expected that the content developer’s profit is highest when only it exerts the monitoring effort, we observe that the scenario where both players exert monitoring efforts results in a win‐win situation. We also analyze the social welfare under all the three illegal content monitoring scenarios.